A clinical evaluation of an ex vivo organ culture system to predict patient response to cancer therapy - Golan, Shay; Bar, Vered; Salpeter, Seth J.; Neev, Guy; Creiderman, German; Kedar, Daniel; Aharon, Sara; Turovsky, Lubov; Zundelevich, Adi; Shahar, Hamutal; Shapira, Hagit; Mallel, Giuseppe; et al. (Frontiers in Medicine, 2023)
Introduction: Ex vivo organ cultures (EVOC) were recently optimized to sustain cancer tissue for 5 days with its complete microenvironment. We examined the ability of an EVOC platform to predict patient response to cancer therapy.: A multicenter, prospective, single-arm observational trial. Samples were obtained from patients with newly diagnosed bladder cancer who underwent transurethral resection of bladder tumor andor from core needle biopsies of patients with metastatic cancer. The tumors were cut into 250-μM slices and cultured within 24 hours, then incubated for 96 hours with vehicle or with paclitaxel and/or gemcitabineintended to treat drug. The cultures were then fixed and stained to analyze their morphology and cell viability. Each EVOC was given a score based on cell viability, level of damage, and Ki67 proliferation, and the scores were correlated with the patients' clinical response assessed by pathology or Response Evaluation Criteria in Solid Tumors (RECIST).The cancer tissue and microenvironment, including endothelial and immune cells, were preserved at high viability with continued cell division for 5 days, demonstrating active cell signaling dynamics. A total of 34 cancer samples were tested by the platform and were correlated with clinical results. A higher EVOC score was correlated with better clinical response. The EVOC system showed a predictive specificity of 77.7% (7/9, 95% CI 0.4-0.97) and a sensitivity of 96% (24/25, 95% CI 0.80-0.99).Conclusions: EVOC cultured for 5 days showed high sensitivity and specificity for predicting clinical response to therapy among patients with muscle-invasive bladder cancer and other solid tumors.